1999
DOI: 10.1081/ada-100101858
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Substance Use Among Military Women and Men

Abstract: This paper examines the relationship between perceived stress (at work, in family or personal life, and from being a woman in the military) and substance use (heavy drinking, illicit drug use, cigarette smoking) among active-duty military women and men. Data were drawn from over 16,000 respondents to the 1995 Department of Defense Survey of Health Related Behaviors Among Military Personnel. Findings indicated substantial substance use and perceived high stress in the armed forces. Further, the relation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 21 publications
9
84
1
1
Order By: Relevance
“…As reported previously (Bray, Fairbank, & Marsden, 1996), both military women and men reported high stress in their military work (about 40%). However, military women (29.3%) were more likely than men (21.5%) to describe their family or personal lives as stressful.…”
Section: Demographic Characteristicssupporting
confidence: 81%
“…As reported previously (Bray, Fairbank, & Marsden, 1996), both military women and men reported high stress in their military work (about 40%). However, military women (29.3%) were more likely than men (21.5%) to describe their family or personal lives as stressful.…”
Section: Demographic Characteristicssupporting
confidence: 81%
“…Some studies have found that women are more likely than men to begin drinking heavily or in problematic ways as an effect of social anxiety (Buckner & Turner, 2009), trauma (Olff, Langeland, Draijer, & Gersons, 2007) and sexual harassment (Gradus, Street, Kelly, & Stafford, 2008). Other studies have found that men have greater tendencies than women toward heavy and problematic drinking in response to stressful life events (Dawson, Grant, & Ruan, 2005), work stress (Bray, Fairbank, &Marsden, 1999) andunemployment (van Praag, Bracke, Christiaens, Levecque, &Pattyn, 2009), and as a method of tension relief (Grotmol et al, 2010). However, such gender differences are not consistently analyzed and, across the studies that do analyze gender differences, are not consistently reported.…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…There is limited evidence suggesting that social support may be more psychologically beneficial for military women. 34,36,37 One study 38 also found that some types of substance use were linked to different stressors in men and women, which may be representative of coping with substances. In the study by Langhinrichsen-Rohling et al, 3 there were also some sex differences regarding which correlates were associated with suicidal ideation in the adjusted model.…”
mentioning
confidence: 99%